2013
DOI: 10.1158/1055-9965.epi-12-0701
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Tailored Navigation and a Standard Intervention in Colorectal Cancer Screening

Abstract: Background This randomized, controlled trial assessed the impact of a tailored navigation intervention versus a standard mailed intervention on colorectal cancer (CRC) screening adherence and screening decision stage (SDS). Methods Primary care patients (n=945) were surveyed and randomized to a Tailored Navigation Intervention (TNI) Group (n=312), Standard Intervention (SI) Group (n=316), or usual care Control Group (n=317). TNI Group participants were sent colonoscopy instructions and/or stool blood tests a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 15 publications
1
82
1
Order By: Relevance
“…Of previous randomized controlled trials comparing a sociopsychologically tailored colorectal cancer screening intervention with an active control, 15,19,20,22,[25][26][27][28][29][30]33 only some reported improvements in screening, 19,25,28,29,34 in most instances based on patient report, 19,25,28,29 suggesting possible misclassification bias. These observations, plus our current findings, raise doubts about the superiority of sociopsychological tailoring to nontailored approaches in promoting colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of previous randomized controlled trials comparing a sociopsychologically tailored colorectal cancer screening intervention with an active control, 15,19,20,22,[25][26][27][28][29][30]33 only some reported improvements in screening, 19,25,28,29,34 in most instances based on patient report, 19,25,28,29 suggesting possible misclassification bias. These observations, plus our current findings, raise doubts about the superiority of sociopsychological tailoring to nontailored approaches in promoting colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,28,29 suggesting possible response bias. There is a need to examine further whether objectively measured colorectal cancer screening improves in response to sociopsychologi...…”
Section: Introductionmentioning
confidence: 99%
“…Navigation interventions have variously used telephone contact with the patient population or referral of patients by primary care physicians to meet with navigators at the time of routine office visits (1)(2)(3)(4). While the current study is aligned with RCTs where a navigator attempted to contact primary care patients (outside routine visits), our navigation approach accommodated face-to-face or telephone contacts.…”
Section: Discussionmentioning
confidence: 99%
“…When Myers and colleagues compared a preference-based intervention with a mailed intervention, where subjects solely received multiple options and no navigation toward preference, the subjects randomized to the preference-based TNI had higher rates than no-intervention controls (TNI, 38%; control, 12%) but the multiple-options group demonstrated a screening rate only 5% lower (38% vs. 33%) (2). Subsequent analyses evaluated the independent effects of the multiple-option mailing versus the telephone navigation for SBT, with the multiple-option mailing associated with increased screening (OR ¼ 2.6, P ¼ 0.001) due to a 29-fold increase in SBT, while telephone navigation was associated with increased screening (OR ¼ 2.1, P ¼ 0.005) due to a 3-fold increase in colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation